2005
DOI: 10.1002/pi.1870
|View full text |Cite
|
Sign up to set email alerts
|

Thermal behavior and flame retardancy of flexible poly(vinyl chloride) treated with Al(OH)3 and ZnO

Abstract: Al(OH) 3 as flame retardant and smoke suppressant for flexible poly(vinyl chloride) was evaluated alone and with ZnO, using thermal analytical techniques, limiting oxygen index and smoke density rating tests. The thermal behavior and flammability of the samples treated with Al(OH) 3 and ZnO were studied by differential thermal analysis and thermogravimetric analysis. The activation energy was calculated by using the Vyazovkin model-free kinetic and Kissinger methods. The results showed that the flameretardant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…For all PVC/ZnO-CA NCs, LOI was calculated, and it was observed that incorporation of ZnO-CA NPs considerably increased LOI of PVC NCs (Table 2) [29].…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…For all PVC/ZnO-CA NCs, LOI was calculated, and it was observed that incorporation of ZnO-CA NPs considerably increased LOI of PVC NCs (Table 2) [29].…”
Section: Thermogravimetric Analysismentioning
confidence: 99%
“…Similar results are obtained in the SDR and the MSD experiment, when the ratio (w/w) of MgCO 3 and AZC is 2:1, the flexible PVC has the best smoke suppression; the SDR of the PVC sample was decreased from 86.9 to 68.3 % and the MSD was decreased from 100.0 to 92.6 %. Compared with the previous work[3,[9][10][11][12], the AZC can also obviously increase the effectiveness of MgCO 3 as flame retardants and smoke suppression for flexible PVC.Tab. 1.…”
mentioning
confidence: 94%
“…Using coupling agents and synergists are good ways to solving these problems. The previous work showed that some synergistic flameretardants such as zinc borate [3], tin additives [9], metal chelates [10][11] and some other metal oxides [12][13] can enhance the effectiveness of Al(OH) 3 or Mg(OH) 2 and then decrease the loading level as flame retardant and smoke suppression for PVC. However, the synergism of MgCO 3 and AZC as flame retardants and smoke suppressant for flexible PVC has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high loading it is essential that good degree of flame retardancy be obtained, but mechanical properties decrease obviously. Using coupling agents and synergists are good ways to solving this problem [4][5][6]. Many elements, such as alloys, organic substances and inorganic compounds including antimony, tin, zinc, copper, iron and molybdenum, have been used in the flame retardation and smoke suppression of PVC.…”
Section: Introductionmentioning
confidence: 99%